Seed replacement in pulses and its impact on productivity - Joshi, Kuhu; Joshi, Pramod Kumar; Khan, Md. Tajuddin; Kishore, Avinash; Shivaswarmy, G. P. (2019)
Pulses are traditionally an important part of the Indian diet and are the major protein source for the poorer as well as the vegetarian populations in the country. Pulse productivity has been stagnant in India due to the widespread use of low quality, farm-saved seeds and low rates of seed replacement. We study the drivers of seed replacement in pulses and its impact on the productivity of pulse farmers in India. We use data on 1764 chickpea and 944 pigeonpea farmers from the nationally representative Situation Assessment Survey of Agricultural Households conducted in 2013. We use probit models to study the drivers of pulse seed replacement and coarsened exact matching to causally study the impact on yields. We find that access to irrigation and credit can increase seed replacement and result in increased pulse productivity.